IMPLEMENTASI EVIDENCE-BASED NURSING MELALUI PELATIHAN TERAPI NONFARMAKOLOGIS UNTUK MENINGKATKAN MUTU PELAYANAN KEPERAWATAN DI FASILITAS KESEHATAN - Sarini Sarini; Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Okti Rahayu Asih; Difa Nur Fadillah (Bajang Institute, 2025)
Evidence-Based Nursing (EBN) has become an essential approach in modern nursing practice by integrating the best available scientific evidence, clinical expertise, and patient preferences to improve the quality and safety of healthcare services. Despite the growing body of evidence supporting non-pharmacological interventions, their implementation in routine nursing practice remains limited due to insufficient knowledge, inadequate clinical skills, and the lack of standardized training among healthcare professionals. This community service program aimed to enhance nurses' knowledge and competencies in implementing evidence-based non-pharmacological therapies to improve the quality of nursing care in healthcare facilities. The program adopted a Participatory Learning and Action (PLA) approach involving 30 nurses through educational sessions, evidence-based practice workshops, clinical demonstrations, simulation exercises, hands-on training, and continuous mentoring. Participants received training on various evidence-supported non-pharmacological interventions, including relaxation techniques, breathing exercises, music therapy, guided imagery, distraction techniques, and therapeutic communication for pain, anxiety, and stress management. Program effectiveness was evaluated using pretest–posttest assessments and structured observation checklists to measure participants' knowledge and clinical competencies. The results demonstrated a significant improvement in nurses' understanding of Evidence-Based Nursing principles, their ability to critically appraise scientific evidence, and their practical skills in applying non-pharmacological interventions during patient care. Furthermore, participants reported increased confidence in integrating evidence-based complementary therapies into routine nursing practice, resulting in more patient-centered, safe, and holistic care. The program also strengthened participants' commitment to continuous professional development and promoted the adoption of evidence-based clinical decision-making within healthcare facilities. This community empowerment initiative demonstrates that training in evidence-based non-pharmacological therapies is an effective, sustainable, and practical strategy for improving nursing competencies and enhancing the quality of healthcare services. Integrating these interventions into clinical guidelines and continuing nursing education programs is expected to foster a stronger evidence-based nursing culture, improve patient outcomes, and support excellence in healthcare delivery.